Corporate Governance Country Assessment : Republic of Lithuania - World Bank (Washington, DC, 2013)
This assessment benchmarks the Lithuanian corporate governance system against the OECD Principles of Corporate Governance and highlights a number of areas where Lithuania's corporate governance system can be strengthened. Lithuania has already invested considerable resources in upgrading its legislation to meet EU Directives, and the legislative and regulatory framework dealing with corporate governance issues is quite robust. The policy recommendations can be grouped under three broad categories: legislative reform, institutional strengthening and voluntary/private initiatives. The legislative and regulatory framework dealing with corporate governance practices has undergone substantial change. The most serious problem is compliance and enforcement. While the assessment highlights several areas where Lithuania's corporate governance system could be strengthened, the priority should be given to the enforcement of existing laws. This report promotes private sector initiatives and capacity building to follow up on the legislative progress on corporate governance reform. It recommends the development of a Lithuanian or regional voluntary code of best practice in corporate governance. The code should be prepared by a task force coordinated by the LSE and made up of public and private sector representatives. In addition, the report proposes the creation of a regional Institute of Directors, to provide training for supervisory board members, disseminate best practice and play a vital role in the dialogue between the public and private sector. Together, these measures give issuers the choice to implement best practice and investors a benchmark against which to measure corporate governance in Lithuania.